Efficient Analytic Approximation of American Option Values - BARONE‐ADESI, GIOVANNI; WHALEY, ROBERT E. (Journal of Finance, 1987)
ABSTRACT This paper provides simple, analytic approximations for pricing exchange‐traded American call and put options written on commodities and commodity futures contracts. These approximations are accurate and considerably more computationally efficient than finite‐difference, binomial, or compound‐option pricing methods.